The role of tumor metabolism in modulating T-Cell activity and in optimizing immunotherapy - Ganjoo, Shonik; Gupta, Priti; Corbali, Halil Ibrahim; Nanez, Selene; Riad, Thomas S.; Duong, Lisa K.; Barsoumian, Hampartsoum B.; Masrorpour, Fatemeh; Jiang, Hong; Welsh, James W.; Cortez, Maria Angelica (Frontiers in Immunology, 2023)
Immunotherapy has revolutionized cancer treatment and revitalized efforts to harness the power of the immune system to combat a variety of cancer types more effectively. However, low clinical response rates and differences in outcomes due to variations in the immune landscape among patients with cancer continue to be major limitations to immunotherapy. Recent efforts to improve responses to immunotherapy have focused on targeting cellular metabolism, as the metabolic characteristics of cancer cells can directly influence the activity and metabolism of immune cells, particularly T cells. Although the metabolic pathways of various cancer cells and T cells have been extensively reviewed, the intersections among these pathways, and their potential use as targets for improving responses to immune-checkpoint blockade therapies, are not completely understood. This review focuses on the interplay between tumor metabolites and T-cell dysfunction as well as the relationship between several T-cell metabolic patterns and T-cell activity/function in tumor immunology. Understanding these relationships could offer new avenues for improving responses to immunotherapy on a metabolic basis.